Karakteristik dan Identifikasi Sumber Daya Perikanan di Perairan Kateman Kabupaten Indragiri Hilir Provinsi Riau - Nurhasan; Rachman. B, Arief; Nur, Novrizal; Sugianto, Sugianto (Samakia : Jurnal Ilmu Perikanan, 2026)
This study aims to identify fisheries resources in the waters of Kateman, which is one of the coastal areas with unique ecological characteristics. This region is known as a center for traditional capture fisheries that still maintains a local wisdom-based fishing system. Kateman features estuarine, pelagic, demersal, and benthic waters. The waters of Kateman have relatively high turbidity due to sediment supply from rivers and strong tidal activities. The presence of a mangrove ecosystem along the water's edge provides protection and spawning grounds for various species of fish, shrimp, and shellfish. The study employs a purposive sampling method, which is a deliberate sampling technique that selects subjects with specific criteria relevant to the study's objectives. A descriptive method is used to describe or portray the characteristics and identification in a factual and accurate manner. Meanwhile, a qualitative method focuses on understanding the meanings, experiences, and perceptions of individuals or groups about fishermen in depth. Based on the data from the identified catches of fishermen in the waters of Kateman, there are 24 species of fish, 3 species of bivalves, and 7 species of crustaceans with notable abundance and biodiversity. These species dominate the area and exhibit wide tolerance to changes in salinity, making it a habitat rich in marine resources. This diversity is vital not only for the local ecosystem but also for the economic sustainability of fishermen who rely on marine resources. The fishermen's catch data indicates that the composition of the catch is dominated by estuarine, pelagic, demersal, and benthic fish species that hold significant economic value for coastal communities. Variations in the types and quantities of catches reflect the influences of oceanographic conditions, fishing seasons, and the characteristics of the fishing gear used by local fishermen. This data also mirrors the level of intensive utilization of fisheries resources, highlighting the need for sustainable management practices to maintain the ecological balance of the waters and the livelihoods of fishermen in the Kateman area.